A highly bendable transparent electrode for organic electrochromic devices - Che, Boyang (2021)
In this article, we report a thin film of polyaniline (PANI)-grafted single-walled/double-walled carbon nanotubes (CNTs) on polyethylene terephthalate (PET) as a transparent electrode for highly bendable electrochromic films. Our results show that the high conductivity of the PANI-CNT/PET electrode brought by its conductive CNT network, as well as the strong conjugation between CNTs and PANI, can be well retained even after 9000 cycles of bending with a bending radius of 0.6 cm, which is superior to that of the most widely used transparent electrode, indium tin oxide (ITO) on PET. By electrodeposition of PANI on the PANI-CNT/PET electrode, the overall electrochromic performance of the PANI-deposited PANI-CNT/PET (PANI/PANI-CNT/PET) is comparable to its PANI/ITO/PET counterpart, whereas after 100 cycles of bending, PANI/PANI-CNT/PET can much better retain its initial electrochromic performance than PANI/ITO/PET. The mechanism for the enhanced bendability is studied via impedance analysis. It shows that the enhancement is mainly due to the robust interface between the PANI-based electrode and active layer. The findings provide a new avenue for rational design of highly bendable electrodes for flexible electrochromic devices.